Residue analysis of sulfametazine in poultry product and its prevention - Yulvian Sani; Raphaella Widiastuti (Indonesian Center for Animal Research and Development (ICARD), 2008)
Sulfamethazine (SMZ) is a sulfonamide preparate widely used in feed to control and prevent diseases, and to promote growth. The use of sulfonamides may lead to residue formation, induce microbial resistance and suspected as a carcinogen. A serial study has been undertaken to investigate the withdrawal pattern of SMZ in meat and liver tissues in order to reduce residue of SMZ. A total of 80 day old chicken were divided into 4 groups consisting: (1) negative control without SMZ; (2) positive control dosing with SMZ for 35 days; (3) treatment-1 was dosed with SMZ for 28 days consecutively three times per week then ceased thereafter; and (4) treatment-2 was dosed with SMZ for 30 days consecutively three times per week then ceased thereafter. A field study revealed that some antimicrobials were detected in poultry meat samples, such as sulfamerazine ( = 2.52 ppb or nd – 12.62 ppb) and sulfamethazine ( = 0.02 ppb or nd – 0.09 ppb). An intragastric dosing of SMZ at 50 mg/kgBB did not affected body weight growth. Both positive control and treated groups showed haemorrhagic enteritis, nottling of capsular surface of liver and pale kidneys. Pathological changes were not found in negative control. Microscopically, pathological changes in liver, intestines and kidneys were found consistently in SMZ treatment. Withdrawal time of SMZ in broilers was between 5 to 10 days. Therefore to produce safe and healthy poultry products, sulfonamides treatment should be withdrawn 5 to 10 days prior to culling of birds and substitution of feed to unmedicated feed within this period is strongly recommended. Key Words: Residue, Sulfametazine, Poultry, Meat, Prevention